User Review Based Content Image Retrieval Using Voronoi Algorithm - Kalaiyarasi, A; Mala, R (International Journal of Computer Sciences and Engineering, 2025)
Relevance input is a fit inquiry change technique in the field of substance based picture retrieval. The key issue in relevance input is how to enough use the input information to improve the retrieval performance. This paper presents a relevance input scheme using Voronoi network model on the other hand input information adoption. Critical images during previous cycles are sensibly incorporated into the current cycle and the chosen critical images can better capture user’s information need.